2017
DOI: 10.1080/21691401.2016.1276923
|View full text |Cite
|
Sign up to set email alerts
|

Lantana camara Linn root extract-mediated gold nanoparticles and their in vitro antioxidant and cytotoxic potentials

Abstract: The Lantana camara Linn root extract derived gold nanoparticles (Au NPs) were characterized by Ultraviolet-Visible spectroscopy, X-ray diffraction, fourier transform-infrared, high resolution transmission electron microscopy, selected area electron diffraction pattern and energy dispersive X-ray analyses. In DPPH assay, the inhibitory concentration (IC) of Au NPs and gallic acid was 24.17 and 5.39 μg/ml, whereas, for cytotoxicity assay, the IC of Au NPs was 17.72 and 32.98 μg/ml on MBA-MB-231 and Vero cells, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The strong surface plasmon resonance (SPR) was located at 566 nm, suggesting the fabrication of stable AuNPs by MEL. Typical AuNPs show peaks at wavelengths between 540 to 570 nm (Das et al 2014; Gómez-Graña et al 2017; Ramkumar et al 2017; Singh et al 2017). There is no noticeable change at the peak after 30 days; we deduced that MEL was acting as an excellent stabilizing agent and hinder the aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…The strong surface plasmon resonance (SPR) was located at 566 nm, suggesting the fabrication of stable AuNPs by MEL. Typical AuNPs show peaks at wavelengths between 540 to 570 nm (Das et al 2014; Gómez-Graña et al 2017; Ramkumar et al 2017; Singh et al 2017). There is no noticeable change at the peak after 30 days; we deduced that MEL was acting as an excellent stabilizing agent and hinder the aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…The IR peaks for amide I and amide II arise owing to carbonyl stretch were reported on the AuNPs synthesized from the same plant 26 . This may be the reason for the reduction of metal ions while using the leaf extract for the synthesis of NPs indicates the binding of the nanoparticles with biomolecules 27 .…”
Section: Resultsmentioning
confidence: 90%
“…Although the effect of L. camara extracts was studied on different cancer cell lines, only a few studies are there so far that investigated the effect of L. camara extract on triple negative breast cancer cells. Ramkumar et al reported cytotoxic properties of L. camara root extract-derived gold nanoparticles on MDA-MB-231 cells (Ramkumar et al, 2017) and in a recent study, El-Din et al showed that methanolic extract of L. camara leaves could exert cytotoxic effect on several cancer cell lines including MCF-7 and MDA-MB-231 breast cancer cells; however, the mechanism of cytotoxicity in breast cancer cell lines was not investigated (El-Din et al, 2022). More recently, Mishra et al reported that extracts of the whole Lantana camara plant harbours cytotoxic effect against triple negative MDA-MB-231 cells although the mechanism of cytotoxicity was unexplored for this cell line (Mishra et al, 2023).…”
Section: Introductionmentioning
confidence: 99%